Nursing interventions for patients with intracranial hypertension: Integrative literature review - de Almeida, Carolina Marques [UNESP]; Pollo, Camila Fernandes [UNESP]; Meneguin, Silmara [UNESP] (Universidad de la Sabana, 2019)
Objective: the study sought to identify, in national and international publications, the principal Nursing interventions aimed at patients with intracranial hypertension. Materials and Method: integrative literature review with search in LILACS, PubMed, Scopus, Web of Science, Cinahal, and Google Scholar databases, from 2013 to 2018. Results: the sample was comprised of seven articles fulfilling the inclusion criteria. Two thematic categories were established for the Nursing interventions aimed at patients with intracranial hypertension: cognitive skills and clinical reasoning, necessary to control neuro-physiological parameters and prevent intracranial hypertension, and evidence-based practices to improve care for neuro-critical patients. Conclusions: intracranial hypertension is an event of great clinical impact, whose complications can be minimized and control through specific Nursing interventions that encompass control of neuro-physiological and hemodynamic parameters and prevention of increased intracranial pressure related with the performance of procedures by the Nursing staff.
Intervenciones de enfermería para pacientes con hipertensión intracraneal: Revisión integradora de la literatura
Intervenções de enfermagem para pacientes com hipertensão intracraniana: Revisão integrativa da literatura
Keywords: Hemodynamic monitoring; Intracranial pressure; Nursing; Nursing care; Nursing care management